Analysis of Noise Level in the Workmanship Workshop Area of PT Berkah Anugerah Inti Semesta Departmental Signs with Control Chart X ̅ and R: Analisis Tingkat Kebisingan di Area Workshop dalam Pengerjaan Rambu Pendahulu Petunjuk Jurusan di PT Berkah Anugerah Inti Semesta dengan Peta Kendali X ̅ dan R - Septia Anggraini; Minto Waluyo (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
PT Berkah Anugerah Inti Semesta, which is engaged in trading, handling, and operational and maintenance services, faces challenges related to exposure to noise levels that can affect workers' health. An analysis was conducted to evaluate the impact of noise on workers and formulate solutions to reduce it. The X̅ and R control map method and fishbone diagram were used to identify noise levels in three workshop areas that have high noise potential. Results showed that some noise values exceeded the threshold, posing a risk to workers' health in the long term. The main cause was identified as a lack of attention to noise management in the production process. The recommendations implemented aim to significantly reduce noise levels, safeguard workers' health, and increase productivity. These results provide strategic guidance for noise management in industrial work environments.